2014
DOI: 10.1159/000368007
|View full text |Cite
|
Sign up to set email alerts
|

The ART Score Is Not Effective to Select Patients for Transarterial Chemoembolization Retreatment in an Italian Series

Abstract: Background: The ART score (a point score for the assessment of retreatment with transarterial chemoembolization, TACE) has been recently developed in Austria to differentiate patients who may benefit from multiple sessions of TACE for hepatocellular carcinoma (HCC) treatment. The primary aim of the study was to test the validity of the ART score in an Italian study cohort. The secondary aims were to evaluate overall survival (OS) and clinical determinants of improved survival in patients treated with multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 18 publications
3
54
1
Order By: Relevance
“…Several studies have reported that the ART score was not a useful tool for guiding decisions on TACE retreatment. In an Italian retrospective analysis in 51 patients with HCC (BCLC stage A or B and Child-Pugh A or B), the ART score was not a significant predictor of survival [59]. A key difference between this study and the original ART score study was that patients may have had longer than 90 days between their first and second TACE, based on the clinical decision of the center.…”
Section: Retreatmentmentioning
confidence: 82%
“…Several studies have reported that the ART score was not a useful tool for guiding decisions on TACE retreatment. In an Italian retrospective analysis in 51 patients with HCC (BCLC stage A or B and Child-Pugh A or B), the ART score was not a significant predictor of survival [59]. A key difference between this study and the original ART score study was that patients may have had longer than 90 days between their first and second TACE, based on the clinical decision of the center.…”
Section: Retreatmentmentioning
confidence: 82%
“…These scores have been proposed as objective and mutually exclusive strategies to select patients for initial as well as subsequent loco-regional therapies based on their capacity to predict long-term survival following TACE. Their prognostic potential, however, has never been compared, a point of major consequence given the emergence of discrepancies from their independent evaluation in separate studies, which has lead to uncertainties in terms of which strategy should be prioritized for clinical use [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Whilst scientifically interesting, the relationship between these scores and patient's overall survival has been questioned following validation in independent cohorts, casting doubt upon their clinical utility [14, 15]. As a result, the use of either score is not advocated within the current management guidelines for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…According to another Italian report [21], ART score had no guidance on whether the patient should conduct TACE retreatment because there was no statistical difference on overall survival between patients with ART score of 0-1.5 and patients with ART scores ≥ 2.5 from their research population, which may be caused by the difference in research population and the relatively smaller number of patients (i.e., n = 51).…”
Section: Discussionmentioning
confidence: 99%